Biochemical and Structural Characteristics, Gene Regulation, Physiological, Pathological and Clinical Features of Lipocalin-Type Prostaglandin D2 Synthase as a Multifunctional Lipocalin - Urade, Yoshihiro (Frontiers in Physiology, 2021)
Lipocalin-type prostaglandin (PG) D2 synthase (L-PGDS) catalyzes the isomerization of PGH2, a common precursor of the two series of PGs, to produce PGD2. PGD2 stimulates three distinct types of G protein-coupled receptors: (1) D type of prostanoid (DP) receptors involved in the regulation of sleep, pain, food intake, and others; (2) chemoattractant receptor-homologous molecule expressed on T helper type 2 cells (CRTH2) receptors, in myelination of peripheral nervous system, adipocyte differentiation, inhibition of hair follicle neogenesis, and others; and (3) F type of prostanoid (FP) receptors, in dexamethasone-induced cardioprotection. L-PGDS is the same protein as β-trace, a major protein in human cerebrospinal fluid (CSF). L-PGDS exists in the central nervous system and male genital organs of various mammals, and human heart; and is secreted into the CSF, seminal plasma, and plasma, respectively. L-PGDS binds retinoic acids and retinal with high affinities (Kd < 100 nM) and diverse small lipophilic substances, such as thyroids, gangliosides, bilirubin and biliverdin, heme, NAD(P)H, and PGD2, acting as an extracellular carrier of these substances. L-PGDS also binds amyloid β peptides, prevents their fibril formation, and disaggregates amyloid β fibrils, acting as a major amyloid β chaperone in human CSF. Here, I summarize the recent progress of the research on PGD2 and L-PGDS, in terms of its “molecular properties,” “cell culture studies,” “animal experiments,” and “clinical studies,” all of which should help to understand the pathophysiological role of L-PGDS and inspire the future research of this multifunctional lipocalin.